The relationship between food security and quality of life among pregnant women - Farnoosh Moafi; Farideh Kazemi; Fatemeh Samiei Siboni; Zainab Alimoradi (BMC, 2018)
Abstract Background Household food insecurity through influencing the quality and sufficiency of nutrition can have considerable effects on individuals' health. Previous studies have shown the relationship between household food insecurity and quality of life among adults, infants, and people of minority ethnicity. However, no studies have been conducted on household food insecurity and quality of life among pregnant women. This study aimed to investigate the effect of food insecurity on quality of life among pregnant women in Qazvin city, Iran. Methods This cross-sectional study was conducted between May 2017 and November 2017 on 394 pregnant women. A random cluster sampling method was used to select eight urban health and medical centers from four geographical regions of Qazvin city, Iran. In the selected centers, pregnant women were recruited using eligibility inclusion criteria. Data was collected using the SF-36 Health-related Quality of Life, Household Food Insecurity Access Scale and a demographic questionnaire for recording the women's gestational and demographic information through interviews. Descriptive and inferential statistics including Chi-square test, one-way analysis of variance with Bonferroni post-hoc test and multiple linear regression were used for data analysis. P < 0.05 was considered statistically significant. Results Food insecurity was reported in 43.9% of the pregnant women. Overall pregnant women's quality of life had the highest score (Mean ± SD) in the domain of 'social performance' (76.4 ± 21) and the lowest one in the domain of 'role limitation due to physical reasons' (60.5 ± 43). Pregnant women with food insecurity had the lowest score in role limitation due to physical reasons domain of quality of life (68.6 ± 40.4, 61.3 ± 45.5 & 51.3 ± 47.7 respectively for mild, moderate and sever food insecurity). The results of multiple linear regression showed that one unit reduction of household food security significantly decreased the total quality of life score by 5.2 score (95% CI: -9.7, − 0.7) among the mild food insecure group, 10.8 score (95% CI: -17.1, − 4.6) among the moderate food insecure group and 14.1 score (95% CI: -19.7, − 8.5) among the sever food insecure group. Conclusions Screening of the household food security status during the primary prenatal care can identify high-risk pregnant women to improve the quantity and quality of their diet. Moreover multi-level actions including policy-making, supplying resources, and providing appropriate services are needed to ensure that pregnant women have access to high-quality foods.